In situ Bragg coherent X-ray diffraction imaging of corrosion in a Co–Fe alloy microcrystal. Issue 7 (27th January 2022) - Yang, David; Phillips, Nicholas W.; Song, Kay; Barker, Clara; Harder, Ross J.; Cha, Wonsuk; Liu, Wenjun; Hofmann, Felix
Abstract : Morphology, 3D lattice strain, and dissolution of a Co–Fe microcrystal was monitored using in situ Bragg coherent X-ray diffraction imaging. Abstract : Corrosion is a major concern for many industries, as corrosive environments can induce structural and morphological changes that lead to material dissolution and accelerate material failure. The progression of corrosion depends on nanoscale morphology, stress, and defects present. Experimentally monitoring this complex interplay is challenging. Here we implement in situ Bragg coherent X-ray diffraction imaging (BCDI) to probe the dissolution of a Co–Fe alloy microcrystal exposed to hydrochloric acid (HCl). By measuring five Bragg reflections from a single isolated microcrystal at ambient conditions, we compare the full three-dimensional (3D) strain state before corrosion and the strain along the [111] direction throughout the corrosion process. We find that the strained surface layer of the crystal dissolves to leave a progressively less strained surface. Interestingly, the average strain closer to the centre of the crystal increases during the corrosion process. We determine the localised corrosion rate from BCDI data, revealing the preferential dissolution of facets more exposed to the acid stream, highlighting an experimental geometry effect. These results bring new perspectives to understanding the interplay between crystal strain, morphology, and corrosion; a prerequisite for the design of more corrosion-resistant materials.